2020
DOI: 10.1002/lpor.201900425
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Quantum Electrodynamics with Second‐Order Topological Corner State

Abstract: Topological photonics provides a new paradigm in studying cavity quantum electrodynamics with robustness to disorder. In this work, the coupling between single quantum dots and the second‐order topological corner state are demonstrated. Based on the second‐order topological corner state, a topological photonic crystal cavity is designed and fabricated into GaAs slabs with quantum dots embedded. The coexistence of corner state and edge state with high quality factor close to 2000 is observed. The enhancement of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
68
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 70 publications
1
68
0
1
Order By: Relevance
“…[16][17][18] Such a behavior is the key advantage over the conventional photonic structures and make them useful for the practical applications. As novel topological phases, higher-order topological insulating (HOTI) phases have recently been discovered in various quantum and classical systems, including crystalline [19] and amorphous materials, [20,21] photonic [15,16,[22][23][24][25][26][27][28][29][30][31] and phononic The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/andp.202100075 DOI: 10.1002/andp.202100075 crystals, [32][33][34][35] and electric circuits. [36,37] As one of the most well-known and simplest second-order topological insulator (SOTI), one might take the SOTI in the systems described by 2D SSH model (see, e.g., ref.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Such a behavior is the key advantage over the conventional photonic structures and make them useful for the practical applications. As novel topological phases, higher-order topological insulating (HOTI) phases have recently been discovered in various quantum and classical systems, including crystalline [19] and amorphous materials, [20,21] photonic [15,16,[22][23][24][25][26][27][28][29][30][31] and phononic The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/andp.202100075 DOI: 10.1002/andp.202100075 crystals, [32][33][34][35] and electric circuits. [36,37] As one of the most well-known and simplest second-order topological insulator (SOTI), one might take the SOTI in the systems described by 2D SSH model (see, e.g., ref.…”
Section: Introductionmentioning
confidence: 99%
“…Topological photonics [1,2] is one of the hottest subfields of photonics for its fundamental importance and promising applications. [3][4][5][6][7][8][9][10][11] The seminal works by Haldane and Raghu [12,13] have shown the ubiquitousness of topological phases manifesting themselves in a broad spectrum of both quantum and classical systems, making breakthroughs in various fields, such as photonics, by transferring the topological concepts of condensed matter physics. [14] After the experimental verification of this idea using square-lattice photonic crystals (PCs) of magneto-optical materials, [15] the photonic versions of the quantum Hall effect, [16] quantum spin Hall effect, [17][18][19] and quantum valley hall effect [20][21][22] have been extensively investigated, mainly focusing on nonzero Berry curvature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2D second-order topological phases have not only 1D edge states but also 0D corner states, [27,28] promising the realization of nanoscale cavities. [9,11] Various invariants, such as the quadrupole moment, [29][30][31][32] Z N Berry phase, [33][34][35] mirror Chern number, [36] nested Wilson loops and polarization, [25,37,38] have been suggested to characterize these new phases. In parallel with these theoretical studies, the higher-order topological phases have been experimentally observed in quantum [39] and classical systems, including microwave circuits, [40] topolectric circuits, [41] acoustic, [42][43][44][45] and photonic systems, [28,[46][47][48] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For further parameter change, gapped edge states appear accompanying with corner or hinge states, which have dimensions lower than the edge states. As an example, the 2D second-order topological insulators generate zero-dimensional corner states as well as 1D edge states immune to the structural defects, enabling robust photonic nanocavities [43] and nanolasers. [44] In photonic practices, one needs multiband edge and corner states, in particular for nonlinear topological photo nics which frequently requires operating over wide spectral ranges.…”
mentioning
confidence: 99%